Dive to the Bermuda triangle - Aslett, Will (United States : BBC Active, 2006)
This program reveals that boats and planes do indeed face real danger in the Triangle but the true threat is often as strange as the wildest theory
Title from title screen
Executive producer, Stephen Wilkinson ; sound, David Brill, Ben Quinn, Mike Kasic ; camera, Paul Jenkins...[et al.]
Keywords: Shipwrecks -- Bermuda Triangle; Bermuda Triangle